2020
DOI: 10.17245/jdapm.2020.20.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Topical anesthesia for stainless steel crown tooth preparation in primary molars: a pilot study

Abstract: Background: Placement of full-coverage restorations such as stainless steel crowns (SSCs) for pulpectomy treated primary molars is essential for successful outcomes. The tooth preparation process for SSCs can cause discomfort to gingival tissues since the crown should be seated 1 mm subgingivally. The purpose of this prospective trial was to compare the effectiveness of subgingival and transmucosal application of topical anesthetics on dental pain during SSC tooth preparation among 6-to 8-year-old children. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…This outcome was expected since, once the patient's discomfort or pain subsided after the prick, infiltration would provide the most profound anesthesia. This is in concurrence with a study by Padminee K (2020), where infiltration anesthesia showed the lowest pain scores as compared to topical anesthetic benzocaine during the conventional SSC preparation and placement 17 . In this study, initial discomfort from infiltration anesthesia sometimes made children uncooperative or fearful.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This outcome was expected since, once the patient's discomfort or pain subsided after the prick, infiltration would provide the most profound anesthesia. This is in concurrence with a study by Padminee K (2020), where infiltration anesthesia showed the lowest pain scores as compared to topical anesthetic benzocaine during the conventional SSC preparation and placement 17 . In this study, initial discomfort from infiltration anesthesia sometimes made children uncooperative or fearful.…”
Section: Discussionsupporting
confidence: 90%
“…This is in concurrence with a study by Padminee K (2020), where infiltration anesthesia showed the lowest pain scores as compared to topical anesthetic benzocaine during the conventional SSC preparation and placement. 17 In this study, initial discomfort from infiltration anesthesia sometimes made children uncooperative or fearful. Therefore, it is recommended that techniques be employed to avoid the need for additional infiltration anesthesia injections in children, which could exacerbate their anxiety and discomfort.…”
Section: Pain Scalementioning
confidence: 87%
See 3 more Smart Citations